(untitled) (LACCEI, 2024)
This study aims to evaluate the quality of surface water, groundwater and tap water through the analysis of physicochemical parameters and hydrochemical composition. For this purpose, surface water, tap water and groundwater samples were collected. The sampling was carried out in the dry season (November 2022). Physicochemical parameters such as pH, electrical conductivity, temperature, and total dissolved solids were analyzed. In addition, the concentration of major ions HCO3–, SO42–, Cl–, NO3–, Ca2+, Mg2+, Na+ and was analyzed. The results indicated acidity conditions in 25% of the surface water samples, mainly in mining environments. Surface water samples are mainly HCO3- - SO42- - Ca2+, while tap water is HCO3- - Ca2+. On the other hand, in groundwater the ions Cl– - Na+ - K+ was predominant. The spatial distribution of the major ions showed a higher amount of SO42- in the mining areas, Los Gringos streams and El Panteón, while along the Santa Rosa river the predominant ion was HCO3-. Groundwater has high Cl– contents in the urban core, which may be related to anthropogenic pollution. These results evidence the need to implement monitoring and control strategies of the human activities carried out in the Santa Rosa city to guarantee the quality of the water in the study area and therefore the safety of its consumers.